Effect of Supplementing Molybdenum, Molybdenum and Sulphur, and Zinc on Mineral Excretion of Sheep Fed with Palm Kernel Cake - Al-Kirshi, Riyadh Abbas (2004)
Feeding high levels of palm kernel cake (PKC) has been reported to cause copper (Cu) toxicity in sheep. The degree of Cu toxicity is generally dependent on type of sheep breed, the form of Cu in the diets, feeding duration and interaction of Cu with other nutrients. This study was specifically camed out to investigate the effect of molybdenum (Mo), sulphur (S) and zinc (Zn) supplementation on the balance of minerals and to relate the findings with the degree of toxicity in Santa In& x Malin crossbred sheep. Twenty male Santa In& x Malin crossbred sheep from 8 months to 1 year of age were divided randomly into 4 groups. The animals were fed the following diets over the 6 months experimental period, PKC (86.2%); guinea grass hay (10%) supplemented with 30 ppm Mo (diet Mo), 20 ppm Mo +lo00 ppm S (diet Mo+S), . 500 ppm Zn (diet Zn) and the control without supplementation (diet Control). Faecal and urine samples were collected during the digestibility trial for mineral analysis. Mineral contents were also analyzed in blood plasma samples throughout the experiment period as well as from liver, kidney, pancreas and bile collected at slaughter. Mo+S or Mo alone and Zn treatments were observed to reduce the Cu level in the liver, kidney, pancreas and bile of the sheep. But Mo+S is more effective in reducing Cu from those tissues, especially the liver. Plasma minerals results showed that both Zn and Mo+S treatments were more effective in reducing Cu, Fe and Mg levels over time. Based on the results of this study, the hepatic Cu content was found to be higher in control group compared with other treatments. However, Mo+S treatment was found to be more effective in controlling and lowering Cu levels. There were significant effect of dietary supplement of Mo+S, Mo and Zn in increasing the loss of endogenous Cu from the body via faeces and urine.